PENGARUH VARIASI PUTARAN CETAKAN PENGECORAN SENTRIFUGAL TEGAK PADA PENGECORAN PADUAN ALUMINIUM TERHADAP KETANGGUHAN IMPAK DAN STRUKTUR MIKRO PEMBUATAN VELG GOKART - Nafiuddin, Ilman; Samsudi, Samsudi (Journal of Mechanical Engineering Learning, 2020)
Centrifugal casting has advantages including more dense castings, low porosity, and high productivity. Factors that influence the results of centrifugal casting such as mold temperature, rotational speed of the mold and the centrifugal force that occurs. The purpose of this study was to determine the effect of the variation of aluminum alloy upright centrifugal casting molds on impact toughness and microstructure in the manufacture of karts wheels. This research is using experimental method. The independent variables in this study were 700 rpm, 800 rpm and 900 rpm mold rotations. The dependent variable is toughness and microstructure. The control variables are mold temperature 250 ° C and pour temperature 750 ° C. Data analysis using descriptive analysis methods and one way ANOVA that is equipped with further tests. Data obtained from the test results in the form of numbers are then presented in tables, graphs and described based on the results of the analysis conducted. The impact toughness test results are that the higher the mold rotation, the greater the toughness value. The highest impact toughness is in the 900 rpm mold rotation specimen of 0.013036 J / mm2. Anova test results obtained the influence of rotational mold variations on impact toughness. Further test results found a significant influence of 700 rpm and 900 rpm mold rotations. The results of microstructure testing are that the higher the round of the mold, the smaller the area of Si grain formed.Keywords: vertical centrifugal casting, variation of mold rotation, impact toughness, micro structures